(3EOGQI GdeMGaX GdGSJKeGQjIs - (3MSfj Ydj(B, (3NQjhTs; (3YHO GdeYWj QVG GQTjO(B, s ((3YeGf(B:s (3OGQ RgQGf(B,s, 2012)
(3GdeaGgje GdYGeI ddeMaXI GdGSJKeGQjI , GdGhQGb GdeGdjI GdeJOGhdI aj CShGb GdfbO h GdeJOGhdI aj CShGb QCS GdeGd GdahQjI , eaghe GdYhGFO h GdeNGWQ h CfhGYgG , GOGQI GdeMGaX GdGSJKeGQjI , HhQUGJ GdChQGb GdeGdjI h HYV CReGJ GdeGdjI GdOhdjI (B: (3cjhe GdGKfjf GdCShO h CReI Shb GdefGN GdchjJj(B.s
Keywords: (3GdESJKeGQs; (3GdGOGQIs; (3GdGhQGb GdfbOjIs